2012
DOI: 10.1021/bi300689t
|View full text |Cite
|
Sign up to set email alerts
|

Concentration-Dependent Structural Transitions of Human Telomeric DNA Sequences

Abstract: Oligodeoxyribonucleotides (ODNs) that have four repeats of the human telomeric sequence d(TTAGGG)(n) can assume multiple monomolecular G-quadruplex topologies. These are determined by the cation species present, the bases at the 5' or 3' end, and the sample preparation technique. In this work, we report our studies of the concentration dependence of the circular dichroism (CD) and the vibrational modes probed by Raman scattering of three previously characterized monomolecular G-quadruplexes: H-Tel, d[5'-A(GGGT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
41
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(44 citation statements)
references
References 52 publications
(90 reference statements)
3
41
0
Order By: Relevance
“…No influence of solution structure was seen for strand concentrations up to 0.4–0.5 uM, although high strand concentration has been proposed to influence solution structure. 38 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…No influence of solution structure was seen for strand concentrations up to 0.4–0.5 uM, although high strand concentration has been proposed to influence solution structure. 38 …”
Section: Discussionmentioning
confidence: 99%
“…Diluted NMR samples gave CD spectra matching low concentration samples, indicating the high concentration used did not influence conformation. 38 …”
Section: Methodsmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11] Human telomeres containing tandem repeats of sequence d(TTAGGG) at their extreme 3 0 -end are the complexes of DNA and proteins located at the ends of the chromosome, which play important roles in protecting chromosomes from fusion and degradation. 17,18 Until now, numerous methods have been used to analyze the structure of the human telomeric G-quadruplex in vitro, such as high-resolution solution state NMR, 5,[8][9][10]19 single crystal diffraction, 20 molecular dynamics (MD) simulations, [21][22][23] circular dichroism (CD), 7,22,[24][25][26] fluorescence, 7,27 differential scanning calorimetry (DSC), 28,29 mass spectrometry, 30,31 photon correlation spectroscopy, 32 atomic force microscopy (AFM), [33][34][35] analytical ultracentrifugation (AUC) 7,36-39 and so on. 17,18 Until now, numerous methods have been used to analyze the structure of the human telomeric G-quadruplex in vitro, such as high-resolution solution state NMR, 5,[8][9][10]19 single crystal diffraction, 20 molecular dynamics (MD) simulations, [21]…”
Section: Introductionmentioning
confidence: 99%
“…The structure and stability of the human telomeric G-quadruplex are determined by the concentration 24 and sequence 9,21 of DNA and the nature and concentration of cations in solutions, [7][8][9]25,40,41 ligands 26,42 and cosolvents. 10,30 Among these conditions, cations play an important role.…”
Section: Introductionmentioning
confidence: 99%
“…If we assume that at low (micromolar) concentrations, both sodium and potassium structures of TQ23 have the same (3+1) topology, then it would be difficult to explain remarkably altered mode of interaction of these conformers with ZnP1 by local differences in the tetrads stacking or tensions in the loops brought about by sodium ions. On the other hand, several studies have demonstrated that a high oligonucleotide concentration coupled with prolonged incubation of the telomeric G-DNA may cause a tremendous change of the initial structure (3234). We believe that the diverse solution conditions of low (this study) and high (NMR) oligonucleotide concentrations as well as applied renaturation procedures may cause the inconsistency.…”
Section: Discussionmentioning
confidence: 99%